Eating disorder and its relationship with psychological distress in the Covid-19 pandemic in Turkey - Demirci, Onur Okan (Progress in Nutrition, 2023)
Background and aim: With the lockdown, panic buying, and stress in the COVID-19 pandemic, people have had a complex and problematic relationship with eating. We aimed to investigate pandemic-related stressful life events and the relationship between eating disorders and psychological distress in students continuing online education during the COVID 19 pandemic. Methods: This cross-sectional study included 770 students. Pandemic-related distress screening questionnaire (P- SLESQ), The Depression Anxiety Stress Scales-21 (DASS-21), and The Eating Disorder Examination Questionnaire (EDE-Q) were used for assessment. Results: Of the 770 participants, 593 (77.0%) were female, 741 (96.2%) were single. 5.6% of the participants had eating disorders, according to the EDE-Q cut-off score. Females reported more frequent disordered eating behaviors or cognitions than males (p <0.001). Also, the students who have medical problems, self or family history of psychiatric disorders, or a history of suicide attempts reported more frequent disordered eating behaviors or cognitions. Psychological distress was found to mediate the relationship between stressful life events experienced during the pandemic and eating disorders (P=0.088). Conclusions: Psychological distress has a significant and positive mediating effect between stressful life events experienced during the pandemic and eating disorders in students continuing online education. The risks for eating disorders outside the time of the COVID-19 pandemic were similar to those during the pandemic. For students in Turkey, the rate of eating disorders was found to be lower in pandemic situations compared to other studies. The findings are discussed in the cultural aspect of the country.